The Therapeutic Potential of Class I Selective Histone Deacetylase Inhibitors in Ovarian Cancer - Khabele, Dineo (Frontiers in Oncology, 2014)
Epithelial ovarian cancer remains the deadliest gynecologic malignancy. Despite advances in treatment, new approaches are needed. Histone deacetylases (HDACs) are a family of enzymes that regulate gene expression by removing acetyl groups from lysine residues on histones and non-histone proteins. Inhibition of HDACs with small molecules has led to the development of HDAC inhibitors (HDACi) that are in clinical use, primarily for hematologic malignancies. Although clinical trials with HDACi as single agents in solid tumors have been disappointing, data from independent labs and recent work by our group show that class I selective HDACi have potent anti-tumor effects in preclinical models of ovarian cancer. This review summarizes the role of HDACs in ovarian cancer and the potential niche for selective class I HDACi, particularly HDAC3 in ovarian cancer therapy.